Mitochondrial Inheritance Is Delayed in Saccharomyces cerevisiae Cells Lacking the Serine/Threonine Phosphatase PTC1 - Roeder, Amy D. (The American Society for Cell Biology, 1998)
In wild-type yeast mitochondrial inheritance occurs early in the cell cycle concomitant with bud emergence. Cells lacking the PTC1 gene initially produce buds without a mitochondrial compartment; however, these buds later receive part of the mitochondrial network from the mother cell. Thus, the loss of PTC1 causes a delay, but not a complete block, in mitochondrial transport. PTC1 encodes a serine/threonine phosphatase in the high-osmolarity glycerol response (HOG) pathway. The mitochondrial inheritance delay in the ptc1 mutant is not attributable to changes in intracellular glycerol concentrations or defects in the organization of the actin cytoskeleton. Moreover, epistasis experiments with ptc1Δ and mutations in HOG pathway kinases reveal that PTC1 is not acting through the HOG pathway to control the timing of mitochondrial inheritance. Instead, PTC1 may be acting either directly or through a different signaling pathway to affect the mitochondrial transport machinery in the cell. These studies indicate that the timing of mitochondrial transport in wild-type cells is genetically controlled and provide new evidence that mitochondrial inheritance does not depend on a physical link between the mitochondrial network and the incipient bud site.